Hindustani music: Thirteenth to twentieth centuries - Bor, Joep; Delvoyce, Françoise; Hervey, Jane; te Nijenhuis, Emmie (Rotterdam Codarts, 2010)
This collection of 25 essays by prominent scholars provides a major overview of the history of Hindustani music from the thirteenth to the twentieth centuries, and the sources that make up this history. The essays are thematically arranged into five parts: (1) The Formative Period, (2) The Modern Period, (3) Musical Instruments, (4) Indian Music and West, and (5) Concepts and Theories.